Surgical Antimicrobial Prophylaxis—Where Do We Stand? - Jha, Anuja; Agrawal, Manju; Hishikar, Rajesh; Jha, Himanshu Shekhar (Annals of the National Academy of Medical Sciences (India), 2021)
Introduction Surgical site infection (SSI) is the commonest preventable health care–associated infection among postoperative cases. Several guidelines are available for surgical antimicrobial prophylaxis (SAP) and other measures which prevent SSI. National Center for Disease Control (NCDC), India, has also provided a guideline for prevention of SSI in 2016. In this study we have compared the NCDC, India, guideline with WHO (World health organization) and American Society of Health System Pharmacists (ASHP) guidelines. The timing of antimicrobial agent administration is the only parameter which is included in all the three guidelines. As per NCDC and ASHP it should be within 60 minutes of incision while as per WHO it is within 120 minutes of incision.Materials and Methods This was a prospective observational study—104 patients undergoing surgery in general surgical ward between January 2016 and June 2017 were included in this study. The NCDC guideline was compared with WHO and ASHP guidelines. Real data comparison was done for those parameters which were included in all the three guidelines.Statistical Analysis Data were analyzed using descriptive methods and chi-square test.Results None of the patients in our study received SAP within 60 minutes of incision. In 70% cases it was administered within 2 hours of incision and in the remaining 30% it was administered after more than 2 hours. There was no significant difference in the incidence of SSI among these two groups.Conclusion NCDC SAP guideline helps in rational use of antimicrobials. Increasing the duration for SAP may be added in the NCDC guidelines. Inclusion of certain additional parameters like weight-based doses and consideration for other comorbidities will help in patient- and procedure-specific SAP. Antimicrobial stewardship should be encouraged in all the hospitals and should follow local antimicrobial resistance pattern. This will assist in therapy decision, policy making, and evidence-based treatment.
Keywords: surgical site infections; surgical antimicrobial prophylaxis; National Centre for Disease Control; India